Facebook Use and Depression: Testing the Role of Social Comparison as a Moderator - Yasin, Bushra (Journal of Peace, Development and Communication, 2021)
This research aimed to investigate the relationship between Facebook use and depression, also to test the role of social comparison as a moderator. The research employed Social Comparison theory. For quantitative research, social survey analysis was used to access the relationship between time spent on Facebook and level of depression. The population selected for the current study was based on the university students. A sampling frame was obtained of all the enrolled students of Foundation University Islamabad. Sample of 384 students was drawn through systematic random sampling. Data was analyzed using hierarchical multiple regression in SPSS 21. All the results were found significant. Findings of the study suggested that there is a significant relationship between time spent on Facebook and level of depression. Moreover, the results also indicated that the social comparison effectively moderate the relationship between time spent on Facebook and level of depression among university students.